2013
DOI: 10.1332/174426413x662572
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evidence assessments of research to inform social policy: taking stock and moving forward

Abstract: There is a tension between conducting comprehensive systematic reviews and completing them in time to meet policy-making deadlines. The ‘rapid evidence assessment’ has been proposed as a solution to this; offering rigorous reviews in a condensed timescale. While used frequently in healthcare, this mode of reviewing presents considerable challenges in social policy. We describe some potential problems and suggest reviewing strategies that can overcome some of them. There are situations, however, in which it may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 23 publications
0
99
0
Order By: Relevance
“…Although the nature of a REA means that it is unlikely to include all the relevant literature related to the search question and some papers may not have been identified, [28] the material retrieved and considered in the review suggests that a reasonable balance between comprehensiveness and timeliness has been achieved. [25] The papers included report empirical data, in the main, and provide some useful insights on the issues involved in supporting staff in caring roles which is an important international issue because a number of countries including England, New Zealand, the USA and the Netherlands have experienced organisational crises in healthcare resulting in failures in care [90] which arise, in part from lack of staff support. For example, Martin and Dixon-Woods [91] argue that if the lessons from a major hospital failure in England are to be learned then the seemingly straightforward solutions that characterise the problem as arising from poor performance in one hospital, or from "bad apple" staff need to be rejected, along with analyses that regard such occurrences as inevitable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the nature of a REA means that it is unlikely to include all the relevant literature related to the search question and some papers may not have been identified, [28] the material retrieved and considered in the review suggests that a reasonable balance between comprehensiveness and timeliness has been achieved. [25] The papers included report empirical data, in the main, and provide some useful insights on the issues involved in supporting staff in caring roles which is an important international issue because a number of countries including England, New Zealand, the USA and the Netherlands have experienced organisational crises in healthcare resulting in failures in care [90] which arise, in part from lack of staff support. For example, Martin and Dixon-Woods [91] argue that if the lessons from a major hospital failure in England are to be learned then the seemingly straightforward solutions that characterise the problem as arising from poor performance in one hospital, or from "bad apple" staff need to be rejected, along with analyses that regard such occurrences as inevitable.…”
Section: Discussionmentioning
confidence: 99%
“…A REA is a tool developed from the systematic review method and involves comprehensive electronic searches of appropriate databases, internet sources and follow-up of cited references. [25] The use of REA is increasing, driven in the main, by the need to engage policy makers, healthcare professionals, and consumers in a timely manner to provide evidence-based recommendations for healthcare practices and policies. [26] A REA can be completed in a shorter period of time than a systematic review, from three weeks to six months for example, [27] and the review reported here was conducted over three months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid, responsive reviews: With lack of timeliness and relevance being most commonly cited barriers to policy use of evidence (Oliver et al 2014) the emergence of rapid reviews has emphasised both methodological and interpersonal solutions for more timely relevant products (Thomas et al 2013). Rapid responsive review services have appeared with key roles for knowledge brokers (Wilson et al 2015;Campbell et al 2011).…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…A non-systematic literature review concerning job retention programmes for people experiencing mental ill-health was conducted following a Rapid Evidence Assessment (REA) technique, which offered a compromise between rigorous and timely synthesis of evidence (Thomas et al, 2013). A search strategy was designed by the research team which involved identifying key terms and synonyms, inclusion and exclusion criteria.…”
Section: Review Of Literaturementioning
confidence: 99%